2019
DOI: 10.1111/jwas.12637
|View full text |Cite
|
Sign up to set email alerts
|

The supplementation of nutrient additives in broad bean‐based diet improved the growth of “crisped” grass carp, Ctenopharyngodon idellus

Abstract: To investigate the effects of supplemental nutrient additives in broad bean‐based diets on growth, flesh quality, and collagen gene expression of grass carp, five diets were prepared, including complete formula diet (control), soaked broad bean (SBB), and three broad bean‐based diets containing 80% broad bean without (BBD1) or with the supplementation of methionine (BBD2), and methionine+vitamins+minerals (BBD3), and were fed to grass carp (171.9 ± 1.1 g), Ctenopharyngodon idellus, for 84 days. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The enhancement in fillet firmness is the most noticeable characteristic in response to a long‐term feeding of faba bean. Besides, the accompanying findings potentially related to the changes in texture quality are as follows: faba bean (1) increased fibre density and number while decreasing fibre diameter, indicating the dominance of myocyte hyperplasia 181,198 ; (2) promoted muscle collagen synthesis by upregulating the expression of col1a1 and col1a2 genes mediated by TGF‐β1/Smad4 signalling 199 ; (3) suppressed oxygen transport, mitochondrial respiratory chain, and creatine metabolism in the muscle, indicating subdued energy metabolic activity 200 ; (4) induced endogenous ROS accumulation and muscle regeneration 168 . Besides, studies in grass carp found that most responses to long‐term feeding of faba bean could be almost reproduced by feeding of pro‐oxidants (vitamin K 3 ) and be abolished by feeding of faba bean combining antioxidants (vitamins C and E) 166,168 .…”
Section: Strategies To Regulate Texture Characteristics In Aquaculturementioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement in fillet firmness is the most noticeable characteristic in response to a long‐term feeding of faba bean. Besides, the accompanying findings potentially related to the changes in texture quality are as follows: faba bean (1) increased fibre density and number while decreasing fibre diameter, indicating the dominance of myocyte hyperplasia 181,198 ; (2) promoted muscle collagen synthesis by upregulating the expression of col1a1 and col1a2 genes mediated by TGF‐β1/Smad4 signalling 199 ; (3) suppressed oxygen transport, mitochondrial respiratory chain, and creatine metabolism in the muscle, indicating subdued energy metabolic activity 200 ; (4) induced endogenous ROS accumulation and muscle regeneration 168 . Besides, studies in grass carp found that most responses to long‐term feeding of faba bean could be almost reproduced by feeding of pro‐oxidants (vitamin K 3 ) and be abolished by feeding of faba bean combining antioxidants (vitamins C and E) 166,168 .…”
Section: Strategies To Regulate Texture Characteristics In Aquaculturementioning
confidence: 99%
“…The enhancement in fillet firmness is the most noticeable characteristic in response to a longterm feeding of faba bean. Besides, the accompanying findings potentially related to the changes in texture quality are as follows: faba bean (1) increased fibre density and number while decreasing fibre diameter, indicating the dominance of myocyte hyperplasia 181,198 168 Besides, studies in grass carp found that most responses to long-term feeding of faba bean could be almost reproduced by feeding of pro-oxidants (vitamin K 3 ) and be abolished by feeding of faba bean combining antioxidants (vitamins C and E). 166,168 This interesting observation has underlined an important but not yet fully explored functional role of ROS during the entire 'crispiness process'.…”
Section: Herbal Plants and Extractsmentioning
confidence: 99%
“…Up to now, the changes in muscle hardness caused by feeding FB not only occur in grass carp, but also in other fish, such as Yellow River carp ( Cyprinus carpio haematopterus ) (Song et al, 2020), Allogynogenetic crucian carp ( Carassius auratus gilello ) (Li et al, 2007) and tilapia ( Oreochromis mossambicus ) (Chen et al, 2014). The amino acid and fatty acid composition were influenced by FB in grass carp (Jiang et al, 2020; Li et al, 2020). Moreover, the FB could markedly enhanced shear force and some texture parameters in muscle in grass carp (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%